Ricardo on the theory of value and money - Takenaga, Susumu (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book is a renovative research work on Ricardo's theory of value and of money, achieved through analysis of Ricardo's original writings, made available in Sraffa's Works. Takenaga argues that Ricardo's economic theory should be understood as a cost theory of value. He begins by re-reading the first chapter of Ricardo's Principles, focusing on the chapter's theoretical structure and definition of labour. He then extends Ricardo's characterisation of the theory of value by situating it in context of debates with other contemporary economists, namely Torrens and McCulloch. In later sections, he argues that Ricardo's theory of money is not a quantity theory, and according to him the causal relation between money's value and its quantity runs from the former to the latter. He closes the book with a discussion of Ricardo's plans to reform the English monetary regime of his time. Providing new insights into essential aspects of Ricardo's economic theory as well as into the history of economic thought, this book will appeal to economic researchers, particularly those studying the classical English economists"--
Keywords: Ricardo, David, -- 1772-1823.; Money; Monetary policy; Finance; BUSINESS & ECONOMICS / Economic History